Hashing Functions can Simplify Zero-Knowledge Protocol Design (too) - Damgård, Ivan B.; Goldreich, Oded; Wigderson, Avi (BRICS Report Series, 1994)
In Crypto93, Damgård showed that any constant-round protocol in which the verifier sends only independent, random bits and which is zero-knowledge against the honest verifier can be transformed into a protocol (for the same problem) that is zero-knowledge in general. His transformation was based on the interactive hashing technique of Naor, Ostrovsky, Venkatesan and Yung, and thus the resulting protocol had very large round-complexity.